Dynamic perforation of ultra-hard high-strength armor steel: Impact experiments and modeling. (September 2019) - Fras, Teresa; Roth, Christian C.; Mohr, Dirk
Highlights: Performed impact experiments on ultra-hard high-strength armor steel using blunt, conical and hemispherical projectiles. Observed perforation through plugging irrespective of projectile shape and velocity. Developed numerical model using modified Johnson–Cook plasticity and strain-rate dependent Hosford-Coulomb fracture initiation model. Obtained good agreement of numerical predictions and experimental results for all types of projectiles. Analyzed perforation process and projectile deformation with the help of numerical simulations and microscopy. Abstract: The dynamic perforation of 3 mm thick target plates extracted from ultra-high strength steel (Mars ® 300) is investigated experimentally and computationally. Projectiles of 8 mm diameter are also extracted from Mars ® 300 plates featuring blunt, conical and hemispherical tips. Using a single stage gas gun, impact experiments are performed with projectile velocities of up to 380 m/s. A minimum impact velocity of about 240 m/s (ballistic limit) was required to perforate the armor steel targets with conical and hemispherical projectiles of a mass of about 14 g. In all successful perforation experiments, the plate targets failed through plugging. At the same time, the conical and blunt projectiles are heavily deformed in a way that their final tip shape resembles that of the hemispherical projectiles. The latter turned out to be slightly more efficient than conical ones in the sense that their exit velocities are approximately 10% higher. Numerical simulations are performed of all impact experiments using the finite element software LS-DYNA. The plasticity model made use of a quadratic yield function with non-associated flow rule, a Swift-Voce strain hardening law and Johnson–Cook type of multipliers accounting for the effects of strain rate and temperature. The stress-triaxiality, Lode angle parameter and strain-rate dependent Hosford-Coulomb fracture initiation model is employed to predict the ductile failure of the Mars 300 steel. Overall, the simulation results are in good agreement with the experimental observations, including the mode of perforation (shear plugging) and the projectile exit velocities. The numerical simulations also show that a ring-like band of localized plastic deformation forms inside the targets with temperatures of up to 700  °C. Fracture initiates from the back face of the plate under biaxial tension, while the cracks propagate through the band of localized plastic deformation towards the impacted front face of the plate, thereby forming a plug as the projectile passes through the target.